Investigation of Electrochemical Dissolving the Amorphous and Nanocrystal Alloys by a Rotating Disk Electrode - Rakhimyanov Konstantin; Ivanova Maria; Rakhimyanov Andrey (MATEC Web of Conferences, 2019)
The electrochemical processing characterized by the absence of force and heat effect on the processed material provides favorable conditions for maintaining unique properties of amorphous and nanocrystal alloys during processing. Understanding the peculiarities of the electrochemical dissolving of the material is possible in studying anode polarization characteristics. The investigations of the anode dissolving of alloys 5ВDSR and 82K3HSR conducted before showed the presence of diffusion limitations connected with the absence of the reaction products removal from the processing zone and supply a new portion of reacting substances. To eliminate the limitations, it is necessary to conduct investigations of the anode behavior by the moving electrolyte which is provided by the rotating disk electrode. It allows controlling the process of ion transfer due to the changes in the anode rotation speed and providing the accessibility of the working sample surface for the electrochemical action. The paper presents the results of polarization investigations of the anode dissolving by using the method of the rotating disk electrode in 10 % neutral solutions of salts NaNO3, Na2SO4 and NaCl. It is established that the dissolving process in the stationary and movable electrolytes is characterized by the presence of zones of slowdown of the anode dissolving process. After providing the electrolyte motion in the processing zone, it became possible to increase the value of the current density.